The role and regulatory mechanism of m6A methylation in the nervous system - Jiang, Lingling; Li, Xiaoheng; Wang, Shasha; Yuan, Zengqiang; Cheng, Jinbo (Frontiers in Genetics, 2022)
N6-methyladenosine (m6A) modification regulates RNA translation, splicing, transport, localization, and stability at the post-transcriptional level. The m6A modification has been reported to have a wide range of effects on the nervous system, including neurogenesis, cerebellar development, learning, cognition, and memory, as well as the occurrence and development of neurological disorders. In this review, we aim to summarize the findings on the role and regulatory mechanism of m6A modification in the nervous system, to reveal the molecular mechanisms of neurodevelopmental processes, and to promote targeted therapy for nervous system-related diseases.